Wandering In Adult Psychiatric Patients: Clinical And Sociodemographic Correlates - Ahmad, Bashir; Farooq, Saeed; Ijaz Hussain; Rehman , Inayat ur (Journal of Pakistan Psychiatric Society, 2006)
Objective: This study was conducted to define the wandering and various factors associated with it in patients admitted to an acute psychiatry unit. Design: Descriptive study Place and duration of study: The study was conducted at the in patients of psychiatry department, Lady Reading Hospital between March 1998 and June 1998 Subjects and Methods: All the patients admitted to psychiatry unit in the period were selected by convenient sampling. They were screened with the help of questionnaire during the course of their psychiatric illness for the wandering behaviour. Wandering was operationally defined for the purpose of the study. Those patients who had one or more episode of wandering were further evaluated to assess their socio demographic and clinical characteristics with the help of a structured interview eliciting the information about precipitants, duration and experience of the wandering. Results: From 240 screened patients a total of 32 patients fulfilled the inclusion criteria, 22 were male & 10 female. 43.74% were living with their parents and40.62% with siblings and 15.62 % with other relatives. In 22 (86%) patients relapse of psychiatric illness precipitated the wandering while in 9 patients (28%) conflict with the family members precipitated wandering. The underlying psychiatric disorders were schizophrenia (32%) followed by major depression (22%) and manic episode (15%). Conclusion: wandering was more common in younger population. Schizophrenia, brief psychosis, depressive illness and dissociative disorders were the common psychiatric disorders associated with the condition. The common preceding factor of wandering behavior was relapse of psychiatric illness. Key words: Wandering, Schizophrenia, Psychiatric diagnosis